Respiratory processes in non-photosynthetic plastids - Renato, Marta; Boronat, Albert; Azcón-Bieto, Joaquín (Frontiers in Plant Science, 2015)
Chlororespiration is a respiratory process located in chloroplast thylakoids which consists in an electron transport chain from NAD(P)H to oxygen. This respiratory chain involves the NAD(P)H dehydrogenase complex, the plastoquinone pool and the plastid terminal oxidase (PTOX), and it probably acts as a safety valve to prevent the over-reduction of the photosynthetic machinery in stress conditions. The existence of a similar respiratory activity in non-photosynthetic plastids has been less studied. Recently, it has been reported that tomato fruit chromoplasts present an oxygen consumption activity linked to ATP synthesis. Etioplasts and amyloplasts contain several electron carriers and some subunits of the ATP synthase, so they could harbor a similar respiratory process. This review provides an update on the study about respiratory processes in chromoplasts, identifying the major gaps that need to be addressed in future research. It also reviews the proteomic data of etioplasts and amyloplasts, which suggest the presence of a respiratory electron transport chain in these plastids.